2021
DOI: 10.1021/acsnano.0c08806
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Boiling–A Scalable Strategy for Self-Assembled Three-Dimensional Graphene

Abstract: Currently, researchers are paying much attention to the development of effective 3D graphene for applications in energy storage and environmental purification. Before commercialization, however, it is necessary to develop a method that allows for the large-scale production of such materials and enables good control over their structural and chemical properties. With this objective, we herein developed a simple method for the formation of large-scale (4 in. wafer) 3D graphene networks via the self-assembly of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…In particular, the appearance of CO and π−π* vibrational excitation (shake up) demonstrated that sulfuric acid opened the cellulose chains after eliminating H + , remapped the carbon structure into graphite crystallites under self-catalysis, and then gradually assembled them into graphene structures. 45,46 Based on the above data, the amount of converted graphene carbon in CNFene was estimated. Figure 4e shows the graphitized carbon content estimated from the difference between the M r (TG) of CNFene and CNF, since the graphitized carbon cannot be decomposed below 800 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the appearance of CO and π−π* vibrational excitation (shake up) demonstrated that sulfuric acid opened the cellulose chains after eliminating H + , remapped the carbon structure into graphite crystallites under self-catalysis, and then gradually assembled them into graphene structures. 45,46 Based on the above data, the amount of converted graphene carbon in CNFene was estimated. Figure 4e shows the graphitized carbon content estimated from the difference between the M r (TG) of CNFene and CNF, since the graphitized carbon cannot be decomposed below 800 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After longer DC, the sp 2 C–C content of DC-CNFene-4 was 57%, which was higher than that of DC-CNFene-1 at 27%, suggesting that the DC process was able to decarbonate the outer CNF chain into sp 2 C–C and derivatives and then bottom-to-top self-assembled into graphene layers on the original surface. In particular, the appearance of CO and π–π* vibrational excitation (shake up) demonstrated that sulfuric acid opened the cellulose chains after eliminating H + , remapped the carbon structure into graphite crystallites under self-catalysis, and then gradually assembled them into graphene structures. , …”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [ 34 ] Copyright 2022, Elsevier. d) Cu‐H binary phase diagram (left) and schematic illustration of the metal/gas eutectic directional solidification (right).…”
Section: Bubbles In Liquid Mediamentioning
confidence: 99%
“…Bubbles form in boiling water has attracted many applications toward the production of materials. [ 34,40–42 ] For example, Ahn et al. proposed an advanced boiling strategy to realize the scalable preparation of foam‐like graphene networks (Figure 2c).…”
Section: Bubbles In Liquid Mediamentioning
confidence: 99%
“…Graphene, as a typical material in the family of two-dimensional materials, has soft carbon-based properties enabling it to display a remarkably high specific surface area, unique electrical, mechanical, and optical properties, high carrier density, and ultrathin form factors, which endow it with great potential for sensing applications. , In 2014, Tour et al first prepared laser-induced graphene (LIG) on a polymer surface with a laser direct writing technique . This method allows easy access to patterned customized LIG, whose porous microstructure and excellent electrical and thermal properties make it a highly effective and flexible electrode active material.…”
Section: Introductionmentioning
confidence: 99%